Characterization of Citrus paradisi peel powder and investigation of lead(II) biosorption - Kucuk, I (Springer, 2024)
This study delves into exploring the potential of agricultural waste materials for effectively reducing lead(II) contamination in water sources. Unlike many biosorbents which undergo costly modifications leading to secondary pollution risks, this research focuses on the unmodified Citrus paradisi (grapefruit) peel (CPP) as a promising biosorbent for Pb+2 ion removal. A comprehensive analysis utilizing various techniques such as FTIR, XRD, boehm titration, point zero charge, BET, TGA, DTA, elemental analysis, AFM, and SEM-EDX was conducted on CPP shedding light on its structural and chemical properties. The biosorption process was scrutinized across multiple parameters including initial metal concentration, contact time, pH, particle size, and solution temperature. Through systematic experimentation covering a range of concentrations and temperatures, kinetic models (Pseudo first order, Pseudo second order, and Elovich) and isotherm equations (Langmuir, Freundlich, and Temkin) were applied to unveil the adsorption behavior. Remarkably, the Langmuir model revealed q(max) = 43.48 mg/g at 310 K and pH 5.6, underscoring the efficiency of CPP in lead removal. Further analysis employing kinetic modeling, notably the pseudo-second order model (R-2 = 0.999), provided insights into the rate of adsorption, affirming its effectiveness. Thermodynamic assessments unveiled an endothermic and spontaneous biosorption process onto CPP, suggesting its feasibility for lead removal in a nature-friendly manner. Moreover, the biosorption mechanism was elucidated through FTIR analysis, elucidating the molecular interactions involved. Overall, the findings of this study underscore the potential of utilizing unmodified agricultural waste, such as grapefruit peel, as a sustainable solution for mitigating lead contamination, offering a cost-effective and eco-friendly approach to water treatment.
Keywords: Agricultural waste; Citrus paradisi peel; Characterization; Biosorption; Lead(II)